Early childhood spirituality in education: Towards an understanding of the distinctive features of young children's spirituality. Issue 5 (2nd September 2016) - Adams, Kate; Bull, Rebecca; Maynes, Mary-Louise
Abstract : Early years education is a holistic endeavour, with some education policies including spiritual development as part of that approach. However, studies exploring the spirituality of young children are scarce, which limits understanding of the phenomenon and its full application in educational settings. Furthermore, nurturing children's spiritual development is a complex matter, compounded by a variety of factors, not least a lack of clarity over what spirituality is. This article initiates a discussion about the possible distinctive features of young children's spirituality. It does so by addressing inherent difficulties in attempting to define spirituality before subsequently reviewing how it is conceptualised in the broader literature, and then in the literature on young children. Implications for policy and practice are considered, arguing that there is a need for more clarity in framing how young children's spirituality may be understood, which needs to be founded on a wider evidence base than currently exists.